Correlation of single-nucleotide polymorphism at interferon-gamma R1 (at Position − 56) in positive purified protein derivative health workers with COVID-19 infection - Mohammad Varahram; Saeid Besharati; Poopak Farnia; Jalaledin Ghanavi; Shima Saif; Jalal Heshmat Nia; Mohammad Reza Madani; Parissa Farnia; Ali Akbar Velayati (International Journal of Mycobacteriology, 2022)
Background: The aim of the present study was to investigate the susceptibility of purified protein derivative (PPD) plus health-care workers to SARS-CoV-2 (COVID-19). For this reason, single-nucleotide polymorphism (SNP) of interferon-gamma (IFN-γ) gene at position +2109 and IFN-γ receptor 1 (R1) at position −56 was assessed in PPD plus group before and after COVID-19 infection (2017–2018; 2020–2021). Methods: The selected study cases (n = 100) that were working in tuberculosis (TB) unite (5–10 years) with PPD positivity >15 mm (16–20 mm) were included in this investigation. Sampling was done twice, once before and after the COVID-19 pandemic. Group A contains 50 samples collected from the GenBank TB laboratory that belong to TB staff before the pandemic (2017–2018). The other sample (Group B; 2021) was collected from the same unite during the COVID-19 pandemic. The SNP in the IFN-γ gene (+2109; 670 bp) and IFN-γ R 1 (−56; 366 bp) was performed using a specific primer and the polymerase chain reaction products were digested using restriction enzyme Fau I and Bts I, respectively. Statistical analyses were used to obtain the frequency of alleles among all studied cases. The confidence intervals (CIs) and t-test were calculated using the SPSS and GraphPad Prism software. Results: In overall, the most frequent genotype in Group A was AA (41/50; 82%) and Group B was 76% (38/50) in position + 2109 (odds ratio [OR] = 0.69, 95% CI, 0.26–1.83, and P = 0.46). Although in position −56, the most frequent genotype in Group A was TT (35/50; 70%) which significantly was than Group B TT (15/50; 30%) (OR = 0.184, 95% CI, 0.78–0.43, and P = 0.00). The frequency of allele A was more in both groups at position + 2109 (OR = 0.815, 95% CI, 0.23–2.86, and P = 0.75), whereas the dominate allele at position −56 was T in Group A (OR = 1.37, 95% CI, 0.62–3.02, and P = 0.42). Conclusion: No significant differences were observed in + 2109 in genotype among Group A and B. The main differences were seen in IFN-γ R1 at position (−56) between Group A and B. Hence, the IFN-γ R1 may play important role in COVID-19 infection. However, more study is needed to clear the IFN-γ correlation to COVID-19 infection.